Genomic diversity, lifestyles and evolutionary origins of DPANN archaea. Issue 2 (9th January 2019) - Dombrowski, Nina; Lee, Jun-Hoe; Williams, Tom A; Offre, Pierre; Spang, Anja
Abstract: Archaea—a primary domain of life besides Bacteria—have for a long time been regarded as peculiar organisms that play marginal roles in biogeochemical cycles. However, this picture changed with the discovery of a large diversity of archaea in non-extreme environments enabled by the use of cultivation-independent methods. These approaches have allowed the reconstruction of genomes of uncultivated microorganisms and revealed that archaea are diverse and broadly distributed in the biosphere and seemingly include a large diversity of putative symbiotic organisms, most of which belong to the tentative archaeal superphylum referred to as DPANN. This archaeal group encompasses at least 10 different lineages and includes organisms with extremely small cell and genome sizes and limited metabolic capabilities. Therefore, many members of DPANN may be obligately dependent on symbiotic interactions with other organisms and may even include novel parasites. In this contribution, we review the current knowledge of the gene repertoires and lifestyles of members of this group and discuss their placement in the tree of life, which is the basis for our understanding of the deep microbial roots and the role of symbiosis in the evolution of life on Earth. Abstract : We review current knowledge on the diversity and genomic potential of the only recently discovered enigmatic and potentially symbiotic DPANN archaea, discuss insights gained from functional studies of host–symbiont systems involving DPANN archaea as well as summarize controversies regarding the placement of the various DPANN lineages in the tree of life and thus the role of this putative radiation in the early evolution of life on Earth.